2008
DOI: 10.1523/jneurosci.4387-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Variant Brain-Derived Neurotrophic Factor (Val66Met) Alters Adult Olfactory Bulb Neurogenesis and Spontaneous Olfactory Discrimination

Abstract: Neurogenesis, the division, migration, and differentiation of new neurons, occurs throughout life. Brain derived neurotrophic factor (BDNF) has been identified as a potential signaling molecule regulating neurogenesis in the subventricular zone (SVZ), but its functional consequences in vivo have not been well defined. We report marked and unexpected deficits in survival but not proliferation of newly born cells of adult knock-in mice containing a variant form of BDNF [a valine (Val) to methionine (Met) substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
174
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(192 citation statements)
references
References 49 publications
14
174
4
Order By: Relevance
“…Using immunohistochemical labeling for the phosphorylated form of TrkB (pTrkB), we found pTrkB to be most highly expressed on immature (PSA-NCAMpositive) neuroblasts (Bath et al, 2008). In the rostral migratory stream pTrkB expression was not detectable on GFAP-positive or NeuN-positive cells (Bath et al, 2008). These effects were identical to what we observed in the DG (Supplementary Figure 1).…”
Section: Altered Bdnf and Trkb Expression Decrease Basal Rates Of Celsupporting
confidence: 77%
See 3 more Smart Citations
“…Using immunohistochemical labeling for the phosphorylated form of TrkB (pTrkB), we found pTrkB to be most highly expressed on immature (PSA-NCAMpositive) neuroblasts (Bath et al, 2008). In the rostral migratory stream pTrkB expression was not detectable on GFAP-positive or NeuN-positive cells (Bath et al, 2008). These effects were identical to what we observed in the DG (Supplementary Figure 1).…”
Section: Altered Bdnf and Trkb Expression Decrease Basal Rates Of Celsupporting
confidence: 77%
“…In previous reports, we have shown that the BDNF Val66Met SNP does not lead to a reduction in total BDNF levels in the whole brain of BDNF Met/Met mice, cultured cortical neurons from BDNF Met/Met mice (Chen et al, 2006), or cortical tissues (Bath et al, 2008). This SNP does lead to a decrease in the trafficking of BDNF to secretory vesicles and the subsequent activity-dependent release of BDNF (Egan et al, 2003;Chen et al, 2004Chen et al, , 2005.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Area densities of subventricular zone (SVZ) BrdU ϩ cells were derived using a method modified from Bath et al (2008). A systematic random sample fraction of 1 ⁄4 serially cut coronal sections, covering ϳ1.54 -0.50 mm relative to bregma, was used.…”
Section: Methodsmentioning
confidence: 99%